Aktivitas Ekstrak Daun Keji Beling (Strobilanthes crispus Blume.) Pada Model Hewan Resistensi Insulin yang Diinduksi Pakan Tinggi Lemak dan Fruktosa - Istiqomah, Aulia Nurfazri (Berkala Ilmiah Mahasiswa Farmasi Indonesia, 2023)
Introduction: Various herbal plants are known to have activity towards increasing insulin sensitivity so that they have the potential to be used for the treatment of diabetes. One of the medicinal plants with this activity is the keji beling leaves (Strobilanthes crispus Blume). Several previous studies have used animal models of insulin resistance due to consumption of high- fat and fructose foods. Therefore, the purpose of this study was to determine the activity of ethanol extract of keji beling leaves on increasing insulin sensitivity in animal models of insulin resistance induced by high-fat and fructose diets. Methods: The method used to create insulin resistance animal models is by giving a high-fat and fructose diet 1800 mg/kgBB preventively for 42 days. The test animals were grouped into 6 groups, namely the negative control group, positive control, metformin 45mg/kgBW, Keji Beling Leaf Ethanol Extract 75mg/kgBB, 150mg/kgBW and 300mg/kgBW. The parameters observed were the value of fasting blood glucose levels on days 0 and 42 and the constant value of the insulin tolerance test (KTTI) on days 0, 21 and 42. Result: Ethanol extract of keji beling leaves had activity towards increasing insulin sensitivity, namely the dose of 75 mg/kgBW with an average reduction value of 12.57, a dose of 150 mg/kg BW with a value of 14.88 and a dose of 300 mg/kg BW with a value of 17.66. Conclusion: The ethanol extract of keji beling leaves has activity in increasing insulin sensitivity with the most effective dose being 150 mg/kgBW.